African States’ desire to emulate the People’s Republic of China developmental path - Theunissen, Esmerelda Theresa (My University, 2021)
The aspirations of Ethiopia and Rwanda to emulate certain aspects of the PRC’s economic transformation and poverty reduction are explored. The PRC developmental path is attractive to Ethiopia as a possible alternative developmental paradigm to shift from agriculture to industrialization and the Rwandan regime’s desire to create jobs in the manufacturing sector with training and employment of Rwandan nationals and the transfer of technology support from the PRC in Rwanda. The research seeks to determine if the PRC development path is advantageous and examine reasons why certain aspects thereof are of interest to the two case studies, in their quest for development. The research is grounded in modernization theory because the course of modernization the PRC embarked on describes specific characteristics of Chinese modernization that relate to socialism and are harmony based and people centred. A qualitative research design was followed to understand the appeal of this development path for the African case studies, while Process Tracing was utilized to comprehend how much the PRC development path is changing growth patterns on the African continent. The PRC development path, although imperfect, its efforts in removing poverty and supporting the poor and marginalized have been more applicable to sub-Saharan Africa. This development path concept has been on the rise and some major themes were introduced and researched in this report
A research submitted to the Faculty of Humanities at the University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Arts in Development Studies, 2021